2021
DOI: 10.3390/agronomy11122535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Se Application on Polyamines and Carbon–Nitrogen Metabolism of Pepper Plants Suffering from Cd Toxicity

Abstract: Previous studies have shown that the application of selenium (Se) can efficiently mitigate the toxic effects of cadmium (Cd) on various crops. The objective of the present work is to decipher the mechanisms responsible for the efficiency of Se against the effects of Cd in pepper plants, with respect to the carbon and nitrogen metabolism. The following were analyzed: the concentrations of anions related with this metabolism, such as nitrates, nitrites, and ammonium, the activities of different enzymes such as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Furthermore, the expression of genes that encode enzymes involved in N metabolism is similarly impacted by Se treatment. Studies have shown that Se application significantly increased the activities of glutamine synthetase (GS) and glutamate synthase (GOGAT) in tea leaves [22], with comparable outcomes observed in research conducted on pepper [23] and lettuce [24]. Sun et al found that Se application could enhance the expression levels of CsGS, CsGOGAT and CsGDH in tea plants [25].…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, the expression of genes that encode enzymes involved in N metabolism is similarly impacted by Se treatment. Studies have shown that Se application significantly increased the activities of glutamine synthetase (GS) and glutamate synthase (GOGAT) in tea leaves [22], with comparable outcomes observed in research conducted on pepper [23] and lettuce [24]. Sun et al found that Se application could enhance the expression levels of CsGS, CsGOGAT and CsGDH in tea plants [25].…”
Section: Introductionmentioning
confidence: 72%